Trials with Catholic Priests and Members of Religious Orders at the Regional Court of Ústí nad Labem between 1953-1960 (Theatrum historiae, 2008)
Negotiations between the state and the church began immediately after the communist takeover in February 1948. The negotiations should have resulted in an agreement of the position of church in Czechoslovakia. However, the negotiations were later precluded by various state imposed anti-clerical precautions. In 1949, the state's real intention was unambiguously revealed – to subjugate or destroy the church in Czechoslovakia. The internment of top representatives of the catholic church and arrests of ordinary priests took place at that time together with state organized anti-clerical actions aimed against the church unity. These aspirations culminated by the politically motivated trials against the church. The Regional Court in Ústí nad Labem tried members of various churches and religious societies together with former members of the Czechoslovak People's Party. This paper is concerned with six selected cases in which Catholic priests were prosecuted. All of them were sentenced to confinement and their spiritual activities were interrupted or even precluded.